2012
DOI: 10.5551/jat.9753
|View full text |Cite
|
Sign up to set email alerts
|

Runx2/Smad3 Complex Negatively Regulates TGF-β-Induced Connective Tissue Growth Factor gene Expression in Vascular Smooth Muscle Cells

Abstract: Aim:Connective tissue growth factor (CTGF), a direct target gene of transforming growth factor-(TGF-) signaling, plays an important role in the development of atherosclerosis. We previously showed that Runx2, a key transcription factor in osteoblast differentiation, regulates osteogenic conversion and dedifferentiation of vascular smooth muscle cells (VSMCs). In this study, we investigated the hypothesis that Runx2 modulates CTGF gene expression via the regulation of TGF-signaling. Methods and Results: Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…RUNX2/Smad 3 interaction stimulated collagen 3 expression in breast cancer cells [61]. Runx2/Smad3 complex negatively regulated endogenous and TGF-beta-induced connective tissue growth factor gene expression in vascular smooth muscle cells [64]. We have found that PC3 cells express Smad −2, -3 and −5 (Additional file 2: Figure S2).…”
Section: Discussionmentioning
confidence: 97%
“…RUNX2/Smad 3 interaction stimulated collagen 3 expression in breast cancer cells [61]. Runx2/Smad3 complex negatively regulated endogenous and TGF-beta-induced connective tissue growth factor gene expression in vascular smooth muscle cells [64]. We have found that PC3 cells express Smad −2, -3 and −5 (Additional file 2: Figure S2).…”
Section: Discussionmentioning
confidence: 97%
“…Evidence from multiple sources indicates that experimental modulation of TGF-​β activity, or TGF-β responses, changes the course of atherosclerosis [45]. Runx2/Smad3 complex negatively regulates TGF-β-induced connective tissue growth factor gene expression in vascular smooth muscle cells [46]. In complicated abdominal aortic aneurysm, TGF-β neutralization increased MMP-12 activity, and MMP-12 deficiency prevented aneurysm rupture [47].…”
Section: Discussionmentioning
confidence: 99%
“…25, 26 We therefore tested if Olfm2 is involved in the Runx2 activity in the SRF-Myocd interaction. Interestingly, PDGF-BB only induced a modest increase in Runx2 expression (1.5 fold) 24 h after the induction (Figure 5A and 5B).…”
Section: Resultsmentioning
confidence: 99%
“…2224 Recent studies have revealed that runt-related transcription factor 2 (Runx2), a key osteogenic transcription factor, serves as a corepressor independent of its DNA binding by interacting with SRF and disrupting the formation of SRF/Myocd complex, which contributes to the phenotypic modulation of SMCs. 25, 26 The precise molecular mechanisms whereby Runx2 interferes with SRF/Myocd complex formation, however, remain largely unknown.…”
mentioning
confidence: 99%